Risk Factors of Transfusion in Anemia of Very Low Birth Weight Infants - Jeon, Ga Won (Yonsei University College of Medicine, 2013)
PURPOSE: Anemia of prematurity is frequent in preterm infants, for which red blood cell (RBC) transfusion remains the treatment of choice. In this study, we attempted to evaluate the characteristics and risk factors of anemia of prematurity, and suggest ways to reduce anemia and the need for multiple transfusions. MATERIALS AND METHODS: Preterm infants weighing less than 1500 g (May 2008-May 2009) were divided into two groups depending on whether they received RBC transfusions (transfusion group and non transfusion group). Hemoglobin (Hb) concentration, phlebotomy blood loss, and the amount of RBC transfusion were analyzed. Risk factors of anemia and RBC transfusions were analyzed. RESULTS: Fifty infants that survived were enrolled in the present study: 39 in the transfusion group and 11 in the non transfusion group. Hb concentrations gradually decreased by eight weeks. In the transfusion group, gestational age and birth weight were smaller, bronchopulmonary dysplasia and sepsis were more frequent, full feeding was delayed, parenteral nutrition and days spent in the hospital were prolonged, and phlebotomy blood loss was greater than that in the non transfusion group. CONCLUSION: Anemia of prematurity was correlated with increased laboratory blood loss, decreased birth weight, prolonged parenteral nutrition, and delayed body weight gain. Accordingly, reducing laboratory phlebotomy loss and parenteral nutrition, as well as improving body weight gain, may be beneficial to infants with anemia of prematurity.